Wheat and triticale whole grain near infrared hyperspectral imaging for protein, moisture and kernel hardness quantification - Orth, Sebastian Helmut (Stellenbosch : Stellenbosch University, 2021)
Thesis (MScFoodSc)--Stellenbosch University, 2021.